EFEKTIFITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAMS ASSITED INDIVIDUALIZATION) TERHADAP HASIL BELAJAR MATERI HIMPUNAN PADA SISWA SMP MARIA MEDIATRIX AMBON - Ngilamele, Maria; Laamena, Christina M; Palinussa, Anderson (Journal of Honai Math, 2019)
This study aims to determine the effectiveness of the cooperative learning type TAI (Teams Assisted Individualization) model according to the results of junior high school mathematics learning in material of set. The method used was quasi-experimental with the post-test only given to control group chosen taking design. Samples were taken using a purposive sampling technique, and two classes by considering students' initial abilities. The control class was treated by using conventional models while the experimental class uses the TAI type cooperative learning model. Data were analyzed by t-test technique. This study revealed that the learning outcomes of students who studied with the cooperative learning model type TAI (67.75) were higher compared to conventional learning models (54.45). Testing the significance of differences with the t-test shows that t count = 2.206 > t table = 2.024, meaning that there are significant differences between the two groups. It can be concluded that the TAI model is more effective as it is reflected on students' higher scores compared to those who were treated with conventional models.